It's not about the wine : the loaded truth behind mommy wine culture - Yvonne, Celeste (Broadleaf Books, 2023)
"Mommy Wine Culture is a symptom of a larger issue: the mental load of motherhood and a systemic lack of support for moms. Mixing research, cultural references, interviews, and the author's sobriety story, this book reveals what's really plaguing mothers and offers tangible tips for evaluating your relationship to alcohol and lightening your load"--